Glacial geomorphology of the Marinelli and Pigafetta glaciers, Cordillera Darwin Icefield, southernmost Chile - Izagirre, Enaut; Darvill, Christopher M.; Rada, Camilo; Aravena Donaire, Juan Carlos (My University, 2018)
This paper presents a glacial geomorphological map relating to two rapidly receding glaciers in the Cordillera Darwin Icefield. The Marinelli marine-terminating glacier and Pigafetta freshwater-terminating glacier are selected to represent different glacial regimes producing different geomorphological records under similar climatic conditions. We combine mapping from satellite and aerial imagery with fieldwork, updating limited previous mapping. The map reveals two principal glacial landform assemblages: (1) a marine-terminating system, dominated by the formation of a large arcuate terminal morainic complex, glaciolacustrine landforms (shorelines) and extended ice-contact topography in the Fiordo Marinelli area; and (2) an assemblage of sequential frontal moraine ridges and outwash plains that formed when the former land-terminating Pigafetta glacier retreated from the Bahia Ainsworth area. Finally, the map is designed as a basis for future chronological campaigns and to enable a refined reconstruction of the glacial history of these two glaciers in a climatologically significant part of the world.
Keywords: glacial geomorphology; cordillera darwin icefield; tierra del fuego; chile; glaciar marinelli; glaciar pigafetta